EFEKTIFITAS EKSTRA MAJENIKU TERHADAP DISMENORE PADA REMAJA PUTRI DI KELURAHAN BELIAN BATAM KOTA - Herawaty Purba, Netty; Fariningsih, Erika; Fransiska Pakpahan, Yohana (NHM PRESS, 2024)
Adolescent and adults who are childbearing age frequently complain of primary or secondary dysmenorrhea. Pelvic pain is most commonly caused by dysmenorrhea. Sharp, sporadic, and spasmodic pain can be categorized as mild, moderate, or severe, depending on how much it interferes with daily tasks or prevents them altogether. Pain lasts for one to three days and starts a few hours before or with the commencement of menstruation. Pharmacological treatments for dysmenorrhea include non-steroidal prostaglandin medications, hormone therapy, and analgesic medications. Nowadays, hormone therapy, NSAIDs, lifestyle modifications, and complementary and alternative medicine are the core treatments for dysmenorrhea. Stretching and aerobic exercise are examples of lifestyle modifications, and peppermint is one of the complementary alternative therapies. The purpose of this study is to determine Majeniku Extra's efficacy in treating dysmenorrhea in young women residing in Belian Village, Batam City. One Group Design Pretest-Posttest experimental design with the Quasi Experiment method is employed in this quantitative study. The purpose of this study is to evaluate aromatherapy's impact. The Wilcoxon test results, which compared the prevalence of dysmenorrhea in adolescents between the pre- and post-test periods, revealed a decrease in the condition with an average score of 13. P value < 0.05 indicated that there was a difference between the two periods. Additionally, the Z min value was found, indicating that teens' dysmenorrhea may be lessened by consuming Majeniku for longer periods of time and more frequently.